L'abandon en formation à distance - Clément Dussarps (Centre National d'Enseignement à Distance, 2015)
This contribution questions learners' dropping out in open distance learning (ODL) through both a socio-affective dimension -i.e. all the feelings and emotions arising from social relations between the different actors involved in the ODL program: teachers, other students, family members - and a motivational dimension. Despite the fact that solitude may induce isolation in distance education, we are trying to understand how learners persevere up to the end of their course, thanks to others, or on the contrary finally drop out. The issue of the initial motivation leading to the student's enrolment will also be approached. The study of this phenomenon is based on a survey, conducted in two phases - at the start and during the ODL program- with 490 distance learners. It shows, in particular, how the gap between expectations and experiences of e-learning can be lead to dropping out. We ultimately intend to establish a list of "risky" profiles, with a high potential of dropping out.